'Living the dream' - Indian postgraduate students and International Student Identity - O'Brien, Paula (2016)
A decline in the number of international students studying in the UK is an issue currently facing UK universities. Competition has steadily increased amongst higher education providers with a greater number of students choosing to study in Australia and the United States. Within this context it is increasingly important for practitioners within the sector to focus more closely on the international student experience. Focus of my research: This research project contributes to the existing literature on the international student experience and moreover international student identity. Higher Education is seen as a site of identity construction for the individual. This research project provides an opportunity to explore the international student experiences of Indian postgraduate students within a new academic culture, their development of support networks, and their search for local employment whilst studying abroad. Identity is understood to be socially constructed; that is, as one’s sense of self and beliefs about one’s own social group as well as others are constructed through interactions in the broader social context such as education and work. This research project has been influenced by more recent developments within psychology and other disciplines which resist the notion of identity as a developmental and linear process. By adopting a social constructionist lens, identity formation is not necessarily considered as a linear phenomenon, emphasising instead the fluid and dynamic nature of identity amongst international students. Identity construction can be located at the individual, relational, organisational levels and moreover the wider society. Essentially identity is seen as constructed and enacted in everyday talk by the student, in their social interactions between themselves and others. Methodology: The research followed seven Indian international students who have undertaken taught postgraduate study abroad for the first time in a UK university and invites them to share their on-going ‘identity-work’ over a 12 month period. The ‘snowball sampling’ criteria included gender; nationality, age, full-time Masters’ students from the same student cohort, with a variation in previous educational background and work experience. Students gave their own individual accounts of their ‘identity-work’ abroad through semi-structured interviews. Within the interviews ‘talk’ is not just approached as an outward manifestation of identity but a site in which identities are constructed and taken up and performed. Identity positions can often be located within ‘interview talk’, and seen as a temporarily occupied coherent identity. This is not to say that identities are ‘just talk’ but that talk is understood as a continuum of meaningful life practices. The methodology employed facilitates the generation of a model of international student identity where identity is seen to emerge in everyday practices. The model encompasses four dimensions: Individual, Relational, Organisational and Societal. Key findings: The study found that study abroad is a site for identity construction. The individual accounts of their lived experience as international students revealed that identity is seen to be temporary and change over time, and Identity emerged in everyday practices both on and off-campus. Identity is drawn from four dimensions, individual, relational, organisational and societal. Societal is significant to the findings and illustrates where identity emerges off-campus during study abroad. The four dimensions of identity change over time and in importance depending on what is going on for the individual. Despite experiencing challenges the participants demonstrated resilience, independence and resourcefulness. Implications/significance of the research: The identity work of international students is acknowledged here as a complex and on-going process. These findings offer a rich understanding of the internationalisation of higher education from an individual perspective. Although some of the problems that students experience are referred to by other researchers, few actually conceptualise them in terms of identity. By conceptualising the international student experience in terms of ‘identity work’ we are able to gain further understanding to ways in which individuals and their environments interact in the social construction of identity formation. This research helps universities, support services and individuals to learn much more about the international student experience so as to more effectively develop the provisions they offer.